Establishment of Rattan Plantations - Muralidharan, E.M.; Sreekumar, V.B.; Kaam, R. (2020)
Rattans are among the most important non-wood forest products of tropical forests. These climbing palms play a significant role in the livelihoods of several rural communities that are engaged in their collection from the forests and their utilisation for the manufacture of products and also as edible shoots. Significant quantities of rattan continue to be extracted from natural forests in an unregulated manner, which has resulted in the loss of genetic diversity and depletion of stocks. To achieve sustainability, it is essential that scientific management of the rattan resources that permits the regeneration of stocks and rational harvesting levels be implemented. Rattan cultivation, which has been practised to a limited extent in countries like Indonesia, Malaysia and the Philippines with varying levels of success, must now be undertaken on a larger scale with respect to key species to cater to the increasing demand for high-quality raw material.